2008
DOI: 10.1007/s10658-008-9402-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Stemphylium vesicarium from different hosts causing brown spot in pear

Abstract: Stemphylium vesicarium (teleomorph: Pleospora herbarum) is the causal agent of brown spot disease in pear. The species is also able to cause disease in asparagus, onion and other crops. Saprophytic growth of the fungus on plant debris is common. The objective of this study was to investigate whether isolates of S. vesicarium from different hosts can be pathogenic to pear. More than hundred isolates of Stemphylium spp. were obtained from infected pear fruits, dead pear leaves, dead grass leaves present in pear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 24 publications
0
29
1
3
Order By: Relevance
“…Species of the genus Stemphylium commonly colonize dead plant materials; such that, there is a paucity of knowledge on the host-specificity of Stemphylium spp. The results of a recent study on the pathogenicity of Stemphylium vesicarium isolates recovered from different host plant species, on pear have shown that only the isolates from pear orchard including pear fruits, dead pear leaves, dead grass leaves present in pear orchard were pathogenic on pear; while, the isolates from onion and asparagus were not pathogenic on pear (Köhl et al 2009). Analysis of genetic variation amongst Stemphylium vesicarium isolates from different host plants has clustered the isolates from pear orchards in a separate cluster (Köhl et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Species of the genus Stemphylium commonly colonize dead plant materials; such that, there is a paucity of knowledge on the host-specificity of Stemphylium spp. The results of a recent study on the pathogenicity of Stemphylium vesicarium isolates recovered from different host plant species, on pear have shown that only the isolates from pear orchard including pear fruits, dead pear leaves, dead grass leaves present in pear orchard were pathogenic on pear; while, the isolates from onion and asparagus were not pathogenic on pear (Köhl et al 2009). Analysis of genetic variation amongst Stemphylium vesicarium isolates from different host plants has clustered the isolates from pear orchards in a separate cluster (Köhl et al 2009).…”
mentioning
confidence: 99%
“…The results of a recent study on the pathogenicity of Stemphylium vesicarium isolates recovered from different host plant species, on pear have shown that only the isolates from pear orchard including pear fruits, dead pear leaves, dead grass leaves present in pear orchard were pathogenic on pear; while, the isolates from onion and asparagus were not pathogenic on pear (Köhl et al 2009). Analysis of genetic variation amongst Stemphylium vesicarium isolates from different host plants has clustered the isolates from pear orchards in a separate cluster (Köhl et al 2009). There are some data available that host-specific toxins produced by Stemphylium vesicarium from pear may play a role in the pathogenicity of the isolates on this host (Singh et al 1999).…”
mentioning
confidence: 99%
“…The pathogenic nature of S. vesicarium isolates from different hosts demonstrated that isolates originating from pear orchards and dead grass leaves, were pathogenic on pear leaves or fruits in bioassays. It was also reported that S. vesicarium from asparagus or onion, were not pathogenic to pear (Kohl et al, 2009).…”
Section: Pathogenicity and Hostmentioning
confidence: 97%
“…In addition to onion, S. vesicarium been found to be pathogenic on garlic (Basallote, 1993), leek (Suheri and Price, 2001), Welsh onion (Misawa and Yasuoka, 2012), asparagus (Falloon, 1987) andEuropean pear (Pyrus communis L.) (Llorente and Montesinos, 2006). Also, in addition to known hosts, the pathogen can cause Stemphylium Blight of Onion: A Review asymptomatic infections and develop as endophytes in the living tissues of various plants (Kohl et al, 2009;Misawa and Yasuoka 2012). In order to prove the pathogenic nature of Stemphylium vesicarium, different workers have adopted different methods on different bulbous vegetables.…”
Section: Pathogenicity and Hostmentioning
confidence: 99%
“…Members of the fungal species Stemphylium are plant pathogens that cause leaf spots in crops such as asparagus ( Asparagus officinalus ), garlic ( Allium sativum ), parsley ( Petroselinum crispum ), pear ( Pyrus communis ) and sugar beet ( Beta vulgaris L.) (Köhl et al , ; Koike et al , ; Hanse et al , ; Gálvez et al , ; Graf et al , ; Tanahashi et al , ). The taxonomy and metabolite production of Stemphylium spp.…”
Section: Introductionmentioning
confidence: 99%